Media fusion and future TV: Examining multi-screen TV convergence in Singapore - Trisha T. C. Lin (International Telecommunications Society (ITS), 2011)
This study examines Singapore's national media blueprint and industry stakeholders' coping strategies in response to multi-screen TV development. The findings show Singapore muti-screen TV development is still at a nascent stage after launching Media Fushion and FutureTV plans in mid 2009. The policymakers play a key role to follow national media blueprint to unify the inter-industry and cross-country collaboration. TV operators and telcos are found to remediate themselves by harnessing the power of internet and mobile technologies for content innovation and distribution. To tackle the complicated convergent issues in multi-screen TV industry, this study proposes to separately regulate the technology-neutral platforms and diverse audiovisual content. It also recommends a pro-innovative policy with the light-touch licensing scheme and loose content regulation to facilitate the development of the next TV.
Keywords: 330; three-screen TV; multi-screen TV; convergence; media fusion; IPTV; mobile TV; cross-platform; TV technologies; TV market; TV policy